Levels of Pesticides in Sediment of Hor Al-Hammar Marshes, Iraq - al-ali, Balqees; Abdullah, Abdulaziz M.; Al-Saad, Hamed T. (Iraqi Journal of Aquaculture, 2022)
The present study was included limitation, distribution, spread and resources of pesticides in water (Dissolved and suspended), sediments from three stations Al-harrir, Al-sulal and Al-burga). This study was extended from January, 2009 to December, 2009 during low tide times. The highest concentrations of pesticides in sediments was recorded for Lindane pesticides in February 497.5 μg/ kg and lowest concentrations 0.01 μg/ kg was found for Dialdrin in March at Al-harrir station and in November at Al-sulal station. Percentage ratio of total organic compounds (TOC) and grain size analysis of sediments was measured and Significant correlation (r = 0.98) were recorded between TOC% and total average of pesticides at tree stations and no Significant correlation were found between silts and total average of pesticides.